Discussing the Study of High Tc Properties of Superconductors with Electron Paramagnetic Resonance (EPR) Spectrometers - Shaltiel, D. (Journal of superconductivity and novel magnetism, 2013)
This work discusses investigations of properties of superconductors with the electron spin resonance (ESR) spectrometers. A significant number of articles were published on this subject. Many authors have tried to explain results derived when applying the (ESR) spectrometers to investigate the properties of superconductors. We show that, except for a single publication, most have missed a very important issue, namely, that it is not possible to study superconducting properties with the electron spin resonance spectrometers unless the mechanism that induces the ESR signals is understood. None of the authors were aware that the mechanisms that induce ESR signals in superconductors must be different than the ESR mechanism that induces signals in compounds that holds spins. Explanations that describe this issue are presented.